2011
DOI: 10.1007/s11242-011-9730-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two-Phase Darcy’s Law with a Thermodynamically Consistent Approach

Abstract: The extended Darcy's law is a commonly used equation for the description of immiscible two-phase flow in porous media. It dates back to the 1940s and is essentially an empirical relationship. According to the extended Darcy's law, pressure gradient and gravity are the only driving forces for the flow of each fluid. Within the last two decades, more advanced and physically based descriptions for multiphase flow in porous media have been developed. In this work, the extended Darcy's law is compared to a thermody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 61 publications
1
44
0
Order By: Relevance
“…By following an argument based on reversibility and dissipation of drainage work in the framework of a thermodynamically based approach (40), it has been shown that relative permeability in the traditional two-phase Darcy formulation (3) has contributions originating from hydraulic conductivity and from dissipative porescale events. This leads to a saturation gradient and, implicitly, a rate dependency for the relative permeability (14), which has been observed many times (e.g., ref. 41).…”
Section: Energy Dissipation and Upscalingmentioning
confidence: 70%
See 3 more Smart Citations
“…By following an argument based on reversibility and dissipation of drainage work in the framework of a thermodynamically based approach (40), it has been shown that relative permeability in the traditional two-phase Darcy formulation (3) has contributions originating from hydraulic conductivity and from dissipative porescale events. This leads to a saturation gradient and, implicitly, a rate dependency for the relative permeability (14), which has been observed many times (e.g., ref. 41).…”
Section: Energy Dissipation and Upscalingmentioning
confidence: 70%
“…When the associated intrinsic relaxation time scale is comparable to the time scale for the general advancement of fluid front propagation or an externally imposed main flow rate (11), the fluid configuration is not in capillary equilibrium (12), leading to the well-known rate dependency of the flow parameters (11,12), which is not captured by the commonly used two-phase extended Darcy description (13,14).…”
Section: Filling Of Pore Spacementioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that interface reconfiguration has an important role in determining the properties and behavior of a multi-fluid porous medium system, attention to this feature is extremely limited (Gray and Miller, 2013;Gray et al, 2015). In some cases, models of two-fluid-phase flow in porous media have been proposed that do not account for either system kinematics or for interfacial stress (e.g., Niessner et al, 2011). Both are necessary components of physically realistic, highfidelity models.…”
Section: Introductionmentioning
confidence: 99%